PEMANFAATAN LIMONEN DARI KULIT JERUK NIPIS DALAM PEMBUATAN LILIN AROMATIK PENOLAK SERANGGA - Kartika, Kartika; Rizki, Fika Awalia; Amanatufahmi, Eva Hardiani; Lestari, Tyas; Sa’diah, Iis (Program Kreativitas Mahasiswa - Penelitian, 2014)
One of untapped potentials of agro-wastes from the manufacture of lime juice squeezed lime juice (Jeniper) in Kuningan is lime peel. The waste is simply thrown away, whereas lime peel can be used or recycled into other products of economic value. A good way is to extract the compound limonene from citrus fruit peel, then limonene is mixed with paraffin to produce aromatic candle that has a variety of advantages such as an insect repellent, air freshener, and as aroma therapy. Aromatic candles from that recycling have a scent that is not too overpowering so it does not cause excessive VOC but remain optimal in the expulsion of insects. In addition, this candle has the same form as candles in general, so the wax remains affordable price if commercialized. This study aims to determine the amount of limonene extract concentration of lime peel that can produce aromatic candle insect repellent (repellen). This study uses experimental design with 4 complete treatment randomized design that is the addition of extracts of limonene 0%, 0.3%, 0.4%, and 0.5%. Subjects were Periplaneta americanus and 15 panellists. The data were then analyzed with One-Way Analysis of Variances (ANOVA) or analysis of variance. Hedonic test results of 15 aromatic candles panellists are as follows: The panellists liked the resulting aromatic candles. In the repellence test there were significant differences between the wax concentration 0%, 0.3%, 0.4% and 0.5%. Wax containing limonene as much as 0.5% have a higher effectiveness in repel insects (repellent) in this case cockroaches. Keywords: Lime peel, Limonene, Aromatic candles, Repellent